2012
DOI: 10.1055/s-0031-1298626
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Protects against High-Fat Diet-Induced Obesity via Regulation of AMP-Activated Protein Kinase Pathways in White Adipose Tissue

Abstract: Emodin is an active herbal component traditionally used in China for treating a variety of diseases. The aim of this study was to examine the effect of emodin on the reducing lipid accumulation in white adipose tissue of high-fat diet-fed rats, and on the regulation of the expression of the genes involved in lipid metabolism to elucidate the mechanisms. After being fed a high-fat diet for two weeks, rats were dosed orally with emodin (20, 40, 80 mg/kg/day) or pioglitazone (20 mg/kg/day), once daily for eight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
0
32
1
Order By: Relevance
“…8, A and B). In fact, a very recent paper also reports that emodin increases AMPK and ACC in hepatocytes and adipose tissues of high fat diet-fed rats and improves dyslipidemia after 8 weeks of treatment (41,42).…”
Section: Discussionmentioning
confidence: 97%
“…8, A and B). In fact, a very recent paper also reports that emodin increases AMPK and ACC in hepatocytes and adipose tissues of high fat diet-fed rats and improves dyslipidemia after 8 weeks of treatment (41,42).…”
Section: Discussionmentioning
confidence: 97%
“…acetosella and R. palmatum contain emodin and chrysophanic acid (Tamayo et al, 2000) which are anthraquinone derivatives reported to have cytotoxic, antitumorigenic, antioxidant properties, and immunosuppressive properties (Yim et al, 1999;Zhang, Lau, Xia, Hortobagyi, & Hung, 1999;Süleyman, Demirezer, Kuruüzüm-Uz, & Akçay, 2002;Tzeng, Lu, Liou, Chang, & Liu, 2012). In addition, Rumex plants contain other anthraquinones like physcion, aloe emodin, rhein, barbaloin, sennoside A, and sennoside B (Wegiera, Smolarz, Wianowska, & Dawidowicz, 2007), and they all showed various pharmacological properties, such as antitumor (Kimura, Sumiyoshi, Taniguchi, & Baba, 2008), antimutagenic (Lee et al, 2005), and antioxidant activities (Demirezer, Kuruüzüm-Uz, Bergere, Schiewe, & Zeeck, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, active compounds naturally co-exist in the diet. In this study, we chose four compounds including apigenin, naringin, quercetin and emodin, all of which were reported to possess the ability of inhibiting adipogenesis [8,11,12,23], to investigate the effect of the four compounds in binary combinations on preventing obesity, which was rarely reported in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, apigenin could activate 5 -adenosine monophosphate-activated protein kinase (AMPK) in a dose-dependent manner, which is known to suppress adipogenesis [8]. Previous reports claimed that emodin enhanced the phosphorylation of AMPK and its primary downstream targeting enzyme, acetyl-CoA carboxylase, and downregulated sterol regulatory element-binding proteins (SREBP1) and fatty acid synthase protein levels in the epididymal white adipose tissue of high-fat diet-fed rats [12]. Compounds such as apigenin and emodin with different modes of action might exhibit synergism resulted from a sequential blockade, concurrent inhibition, or complementary inhibition [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation